Urban Church's Contextual Response to Urban Toxicity with An Intersubjective Approach - Nugroho, Sandi; Sudhiarsa, Raymundus I Made; Firmanto, Antonius Denny; Ligawan, Andry Saputra (International Journal of Indonesian Philosophy & Theology, 2024)
The post-pandemic period is full of challenges for urban churches in Surabaya. While having to survive, he must also continue interpreting his presence as an extension of the mission of the Kingdom of God. Rumah Singgah is a manifestation of GKI Pregolan Bunder's participatory-transformative diakonia mission as an ecclesiological response to the urban context in Central Surabaya. This mission is based on the redemptive work of Christ. It runs on an intersubjective path where all parties are subjects who continue to actively participate in transforming life for the sake of shared well-being. Through this qualitative phenomenological research, the researcher wants to propose an intersubjective approach as a new alternative to the urban mission in Surabaya, especially in the new post-pandemic era. Researchers conducted interviews based on Ricouer's scheme regarding life events in Rumah Singgah. The results found that intersubjective relations are relevant for building interactive and dialogical encounters between the church and surrounding communities.